The EU urban policy in the period 2007–13: lessons from the Spanish experience. Issue 1 (1st January 2018) - De Gregorio Hurtado, Sonia
ABSTRACT: Urban issues have been under the policy attention of the European Union (EU) from the late 1980s. Its influence has been particularly significant in countries that had not developed an explicit urban national policy. This is the case of Spain, in which specific instruments aimed to address urban challenges co-funded by the Structural Funds have been developed over the last four programming periods of the Cohesion Policy. These instruments have been the following: URBAN (1994–99); URBAN II (2000–06); the Iniciativa Urbana (IU) (2007–13); and the Integrated Sustainable Urban Development Strategies (ISUDS/EDUSI) (2014–20). So far they have been the only explicit initiatives of urban regeneration that have operated at a national scale in the country. This fact, together with the sustained experience in implementing these kinds of instruments, points to Spain being an interesting case study in which to understand the evolution and contribution of the urban dimension of Cohesion Policy from 1994 to the present. In this context, the IU emerges as particularly relevant because it has worked as a nexus between the two rounds of URBAN and the ISUDS that are currently being implemented. It is also relevant because it continued the implementation of the URBAN method in Spain explicitly through 46 programmes of urban regeneration that were developed in all the regions (Autonomous Communities), something that did not happen in any other member states in the period 2007–13. Building on the literature on the contribution of URBAN to the practice of urban regeneration in the country, this study develops an in-depth analysis of the IU. The research has allowed the identification of the relevant lessons aimed to inform the implementation of the 173 ISUDS that are being developed at present in Spanish cities. These lessons can also contribute to the Spanish Urban Agenda (in progress) and, at the EU level, to the definition of the urban dimension of Cohesion Policy for the post-2020 period and its implementation in the member states.